Factores sociales y familiares que determinan el débil sentido de pertenencia de los residentes a su familia en el centro de atención residencial hogar San José. Trujillo 2015. - Miñano Lázaro, Kerlyn Lizbeth (2016)
The research entitled "Social and family factors that determine the weak sense of belonging of residents to their families in residential Care Home San Jose, Trujillo - 2015, arises from the need to know what factors are influencing not the process of social and family reintegration is made. The residence time leading into the institution, as the family is involved and how it will generate a reception area for their children is investigated, but especially how much interest shows the family for change and help improve the processes of family relationships relation to the residents of the institution. One theory behind the study is the general theory of systems theory put forth by Ludwig Bertalanffy in 1925 on the so-called "open system" where those internal or external structures in humans or their companies involved have a intimidates relationship with the environment or environment in which they are immersed. Likewise, this theory allows us to consider that the family is a powerful tool, which builds up living in a complex system, allowing some predicting future behaviors. This theory in relation to the study being done, has allowed to know and assess the socio family in which residents have lived and formed, with a history to explain current behaviors and certain behaviors of their family formation, as well as known characteristics of the family environment, enabling to understand and meet certain family events that give rise to own both parents and / or guardians behavior. The research is descriptive; made use of methods: inductive - deductive, and statistical; observation guide, interview guide: along with the techniques of observation, interview and test instruments as also was used. This research was conducted based on the cases of residents housed at the Center for Residential Home Care San Jose, where the target care population are children and adolescents aged 6 to 18 who are under investigation protect and abandonment. The results confirm that family factors are important elements affecting about family affiliation, the sense of belonging, and which in the study population is not given properly, also because of social factors affecting and affect social and family formation of each person. Also this accompanied by negative models of parenting, inadequate relationships that strengthen and get larger problems that already exist within each family and that makes it more dysfunctional, leading to children decide to spend more time outside his home, also generating behaviors inadequate because of the lack of care and family formation.